The behavior of polymer-bentonite interface under shear stress. (10th July 2020) - Li, Manjun; Fang, Hongyuan; Du, Mingrui; Zhang, Chao; Su, Zhan; Wang, Fuming
Highlights: The direct shear behavior of the polymer-bentonite interface was investigated. Normal stress, moisture content, and density are treated as different conditions. A large-scale multi-functional direct shear apparatus was used. Digital image correlation (DIC) was employed to observe the development of cracks. Abstract: As new building materials, polymers have gradually been used in infrastructure engineering applications such as civil engineering, water conservancy, and highway repair engineering. The shear behavior of the interface between polymer and bentonite plays an important role in the analysis of the interactions at the interface. This paper investigated the direct shear behavior of polymer-bentonite interface under various conditions. The shear stress, horizontal displacement, and failure mode were observed under four initial normal stresses, four values of the moisture content of bentonite, and three polymer densities by utilizing a large-scale multi-functional direct shear apparatus and a digital image correlation (DIC) system. The results show that the shear strength of polymer-bentonite interface is higher than that of the pure bentonite. An increase in either initial normal stress or polymer density improves the shear strength of polymer-bentonite interface, while a higher moisture content of bentonite reduces it. Moreover, the polymer-bentonite composite fails in the bentonite phase or at the interface between polymer and bentonite. Finally, the concepts of the equivalent angle of internal friction and the equivalent cohesion of the polymer-bentonite interface are proposed and applied to the analysis of the interaction between the polymer and bentonite.